Knowledge towards the health impacts of climate change and associated factors among undergraduate health sciences students in Amhara region: a multi-centered study - Alemayehu, Meron Asmamaw; Workie, Sewnet Getaye; Belew, Makida Abate; Agimas, Muluken Chanie; Derseh, Nebiyu Mekonnen; Abuhay, Habtamu Wagnew; Berihanu, Redeat; Kinfe, Fasika Terefe; Abebe, Haymanot Assefa; zemene, Sophiya; Bazezew, Astewil Moges (Frontiers in Environmental Health, 2024)
Background: Increased knowledge about the health impacts of climate change would motivate health students and health professionals to adopt sustainable healthcare practices, design climatecentered health programs, help build climate-resilient health systems, and ultimately contribute to the global effort of mitigating climate change.Method: An Institution-based cross-sectional study was conducted among Universities in the Amhara region. A total of 616 undergraduate health science students were included from three Universities. A validated, self-administered structured questionnaire was used. Data were analyzed using STATA™ version 14.0. A Logistic regression model was used to identify the factors associated with the health impacts of climate change. A P-value less than 0.05 was considered to be statistically significant.Result: Only 48.5% (95% CI: 44.6, 52.4) of students had good knowledge regarding the health impacts of climate change. Sex of the student -male (AOR=1.44, 95% CI: 1.032, 2.023), University (AOR= 0.534, 95% CI: 0.360, 0.792), and Department -comprehensive Nursing, (AOR= 0.264, 95% CI: 0.117, 0.592), Midwifery (AOR = 0.201, 95% CI: 0.085, 0.476), and Medical Laboratory (AOR = 0.151, 95% CI: 0.055, 0.413) were significantly associated factors.: The knowledge of the health impacts of climate change among health science students was low. Sex, University, and Department were the associated factors. Hence, undergraduate health science programs should incorporate at least the fundamental details of climate change. Universities should also develop and use a harmonized curriculum.